Inconsistent Yield Response of Forage Sorghum to Tillage and Row Arrangement - Nieman, Christine C.; Franco, Jose G.; Raper, Randy L. (Agronomy (Basel), 2024)
Forage sorghum is an alternative source for biofuel feedstock production and may also provide forage for livestock operations. Introducing biofuel feedstock as a dual-use forage to livestock operations has the potential to increase the adoption of biofuel feedstock production. However, additional technical agronomic information focusing on tillage, row arrangement, and harvest date for forage sorghum planted into pasturelands intended for dual use is needed. Three tillage treatments, disking and rototilling (RT), chisel plow (CP), and no tillage (NT), and two row arrangement treatments, single-row planting with 76.2 cm rows and twin rows of 17.8 cm on 76.2 cm centers, were tested for effects on forage sorghum yield in a 3-cut system. This study tested two sites in Booneville, AR, from 2010 to 2012. Several interactions with year were detected, likely due to large precipitation differences within and among years. The year greatly affected the yield, with greater (p < 0.05) yields in year 1 compared to years 2 and 3 in both locations. No till resulted in lower yields in some years and harvest dates, though no clear trend was detected among tillage treatments over years. Twin rows generally did not improve yield, except for the third harvest date at one location. No strong trends for tillage or row arrangement effects were observed in this study. Inconsistencies may have resulted from the strong influence of year or interactions of multiple factors, which may challenge producers interested in utilizing forage sorghum for biofuels and livestock feed.